(untitled) (Revista Científica Integrada, 2024)
Objective: To report the experience and learning of nursing undergraduates when participating in the situational diagnosis process in a health region in the interior of the state of Piauí, Brazil. Method: Descriptive study, experience report type, about the participation of nursing students in a regional health planning workshop, held in August 2022, involving municipal managers from a health region in Piauí. Results: The workshop provided moments of collective, integrated, and participatory construction of the situational diagnosis of the health region, resulting in the identification, and listing of priority health problems/needs based on local information and evidence. It is known that regional planning is a challenging task for managers at different levels of management, whether due to the difficulty of planning together or due to inexperience with the integrated health planning process itself. Conclusions: During the experience, it was possible to ratify the importance of knowledge about public health planning even during graduation, expanding theoretical and practical knowledge through the unique opportunity of insertion into the dynamics of operation and recognition of the challenges of the Unified Health System.